2020
DOI: 10.1111/pbi.13492
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐scale assembly of allotetraploid Brassica juncea (AABB) elucidates comparative architecture of the A and B genomes

Abstract: Summary Brassica juncea (AABB), commonly referred to as mustard, is a natural allopolyploid of two diploid species—B. rapa (AA) and B. nigra (BB). We report a highly contiguous genome assembly of an oleiferous type of B. juncea variety Varuna, an archetypical Indian gene pool line of mustard, with ~100× PacBio single‐molecule real‐time (SMRT) long reads providing contigs with an N50 value of >5 Mb. Contigs were corrected for the misassemblies and scaffolded with BioNano optical mapping. We also assembled a dra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 72 publications
(114 reference statements)
2
46
0
Order By: Relevance
“…3a and 7 ), by consistent syntenic gene ordering (Supplementary Fig. 8 ) using genome-ordered graphical genotypes 28 , and by the good collinearity of SY to those of B. rapa 29 and B. nigra 30 and other previously reported Brassica genomes 19 , 25 , 31 (Supplementary Fig. 9 ).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…3a and 7 ), by consistent syntenic gene ordering (Supplementary Fig. 8 ) using genome-ordered graphical genotypes 28 , and by the good collinearity of SY to those of B. rapa 29 and B. nigra 30 and other previously reported Brassica genomes 19 , 25 , 31 (Supplementary Fig. 9 ).…”
Section: Resultssupporting
confidence: 66%
“…SY is a yellow-seeded landrace of B. juncea and represents a new form evolved from hybridization between two big gene pools. Therefore, SY is different from previously sequenced stem 19 and Indian 25 mustard. The chromosome-scale reference genome of SY, in conjunction with re-sequencing of 480 accessions, captured major genetic variation and allowed detailed reconstruction of the evolutionary and domestication history of this diverse ancient crop species.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Brassica species are ideal models for studying polyploid genome evolution [53], and B. juncea has the yellow-seeded trait genus naturally [8]. Therefore, we used the genome sequence of B. juncea [1,54] to perform comprehensive transcriptome and metabolic profiling of developing seeds in yellow-and dark-seeded B. juncea. In this study, our results identified differentially abundant metabolic compounds, including phenolic acids, flavonoids, lipid compounds, hydroxycinnamic acids, and novel unknown compounds.…”
Section: Introductionmentioning
confidence: 99%